Digital competence, new perspectives for teaching in contexts of social isolation - Cruz Cobeñas, María Amelia (2020)
The article reviews the problem of digital competences from the digital constructivist learning approach for digital empowerment from formative education of the dimensions: (a) personal, (b) ethical, (c) professional, as opposed to the structuralist definition or functionalist of the connectivist approach, which prioritizes the professional and functional dimension of the competences in the use of information and communication technologies. Digital competences are established as the skills to achieve integration, accessibility, employability and equity of digital communities, valued in the context of the current pandemic and in virtual education, doors of a future of sustainable health and citizenship.